Optimalisasi Daya Saing UMKM Dengan Sertifikasi Halal di Kecamatan Sumberlawang, Sragen - Putri Rizka Citaningati (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting economic growth and employment in Indonesia. However, many MSMEs still face challenges in improving product competitiveness, market access, and consumer trust. One of the strategic efforts to address these challenges is through halal certification. This community service program aimed to enhance MSME competitiveness by improving participants’ understanding and readiness in obtaining halal certification. The program was conducted through socialization, training, mentoring, and evaluation activities. The materials covered halal assurance systems, halal certification procedures, business legality, and the strategic benefits of halal certification for business development.